A whole new ball game: Stem cell-derived epithelia in the study of host–microbe interactions. (February 2016) - Leslie, Jhansi L.; Young, Vincent B.
Abstract: Recent advances in developmental and stem cell biology have resulted in techniques that enable the generation and maintenance of complex epithelium in vitro. While these models have been utilized to study host development and disease, a renewed appreciation of host–microbe interactions has sparked interest in employing these new techniques to study microbes at the epithelial interface. Here we review the current advances in host–microbe interactions that have resulted from experiments using these complex epithelia. Furthermore we highlight aspects of these techniques that warrant further development to facilitate the study of host–microbe interactions. Highlights: Stem cell-derived model epithelia recapitulate aspects of the GI tract. These models are an intermediate between polarized cell lines and animals. Salmonella Typhimurium, Helicobacter pylori, and Clostridium difficile have been studied using these systems.